Mapping the Future of AI-Driven Digital Transformation in SMEs: A Bibliometric and Conceptual Framework Analysis Towards Sustainable and Inclusive Innovation - Umar Yeni Suyanto; Ratna Rosita Pangestika; Kinanti Puja Prameswari; Heni Setiyaningsih (Program Studi Pendidikan Ekonomi FKIP Universitas Lambung Mangkurat, 2026)
The integration of Artificial Intelligence (AI) into Small and Medium Enterprises (SMEs) has become a critical lever for achieving resilience, efficiency, and long-term sustainability in the digital era. However, despite AI’s transformative potential, empirical evidence suggests a persistent gap between technological capabilities and actual adoption within the SME sector. This study employs a bibliometric analysis using VOSviewer with the keywords